2004
DOI: 10.1002/app.20148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water on the oxygen barrier properties of poly(ethylene terephthalate) and polylactide films

Abstract: ABSTRACT:The aim of this work was to study the variations in the oxygen diffusion, solubility, and permeability coefficients of polylactide (PLA) films at different temperatures (5, 23, and 40°C) and water activities (0 -0.9). The results were compared with the oxygen diffusion, solubility, and permeability coefficients obtained for poly(ethylene terephthalate) (PET) films under the same experimental conditions. The water sorption isotherm for PLA films was also determined. Diffusion coefficients were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 31 publications
3
98
0
Order By: Relevance
“…Because PLA is permeable to oxygen, response times can be fast. 42,43 PLA nanoparticles are known to degrade over 2 years time because of acid-catalyzed ester hydrolysis. The polymer molecular weight decreases slowly for 5 weeks, then more rapidly thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…Because PLA is permeable to oxygen, response times can be fast. 42,43 PLA nanoparticles are known to degrade over 2 years time because of acid-catalyzed ester hydrolysis. The polymer molecular weight decreases slowly for 5 weeks, then more rapidly thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…PLA processed barrier properties that were higher than those of PE, PP and similar to PS but lower than those of PET ( Figure 10). Auras and coworkers [50,51] studied the barrier properties of PLA and compared them with those of PET and PS. They showed that the permeability coefficients of CO 2 , O 2 , N 2 , and H 2 O (g) for PLA were lower than that of PS, but higher than that of PET.…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…We suggest that this behaviour might be caused by the different chirality of the Biophan  sample, because the crystallization kinetics are strongly dependent on the D-and L-content of the copolymer. 29 Solvent-induced crystallization has already been described for the semi-crystalline polyester PET, 40,46 -48 in particular by Serad et al 40 and by Ouyang et al 48 who showed the crystallization of PET in contact with acetaldehyde and acetone, respectively. Ouyang and Shore 49,50 showed for the solvent-induced phenomenon that the sample dimensions increased after the sorption of the solvent due to swelling of the polymer.…”
Section: Samplementioning
confidence: 99%